EVALUATION OF THE EFFICIENCY OF THE LUBRICATION OF OILS WITH CARBONFLUORIDE ADDITIVES IN NON-STATIONARY FRICTION REGIMES - Melnyk, Volodymyr; Leusenko, Darya; Mamai, Bohdan (Problems of Friction and Wear, 2023)
The results of the study of the effect of carbonofluoride additives on the lubricating effect of aviation oils VNIINP-50-1-4u, IPM-10 are presented; MS-8p, industrial oils I-20A, IGP-18 and automotive oil M-10G2K in non-stationary friction modes. The introduction of KF additives into lubricating media significantly reduces, and in some cases completely eliminates, the temporary deterioration of the lubricating effect in non-stationary modes due to the high adsorption properties and chemical activity of carbonofluorides.